Complete Closed Genome Sequences of Three Salmonella enterica subsp. enterica Serovar Dublin Strains Isolated from Cattle at Harvest - Harhay, Dayna M. (Microbiol Resour Announc, 2018)
Salmonella enterica subsp. enterica serovar Dublin is a host-adapted pathogen for cattle that can cause invasive disease in humans. To facilitate genomic comparisons characterizing virulence determinants of this pathogen, we present the complete genome sequences of three S. Dublin strains isolated from bovine sources at harvest.